The textbook, its concept and educational importance (Journal of the College of Basic Education, 2022)
School books are considered one of the important means in the educational process, as it is a pregnant container for the educational subject, and it is the reference from which the learner draws the primary source of learning, so it was taken into account in preparing a number of educational, pedagogical and scientific settings so that it is at the level of new and effective curricula in the hands of learners. The textbook is one of the most effective educational means Efficiency in helping the teacher and the learner in performing their mission in the school and therefore it should not be neglected in any educational program, it is a basic evidence of teaching methods and the process of evaluation, as wellThe researcher has reached several conclusions, including:If the textbook is used in art and moderation, it is the best way to teach.1.2If the textbook is made appropriately by the author and formulated it in a clear .3linguistic style and with an educational skill, the teacher will make it easier to improve his method of the educational process